Associations between dietary inflammatory index (DII) scores and attention deficit hyperactivity disorder (ADHD) in children - Fatemeh Navab; Khadijeh Abbasi; Hajar Heidari; Reza Ghiasvand; Cain C. T. Clark; Mohammad Bagherniya; Shirin Hassanizadeh; Mohammad Hossein Rouhani (Scientific Reports)
Abstract Attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders, yet its underlying mechanisms remain unclear. Genetic, family history, nutritional, lifestyle, and inflammatory factors are considered as contributing factors of ADHD. The dietary inflammatory index (DII) could be used to determine whether a diet has an inflammatory potential. Therefore, the purpose of this study was to find out if DII scores and ADHD were related. This study included 500 Iranian children aged 4–12 (200 ADHD cases and 300 healthy controls). Food frequency questionnaires (FFQs) consisting of 168 items were used to determine dietary intake. DII scores were calculated using data from D-FFQ. Energy-adjusted DII (E-DII) scores were calculated using standardized z-scores for each food item, following established protocols. Analysis of covariance (ANCOVA) assessed energy-adjusted dietary intake across DII tertiles. Multivariable logistic regression estimated ADHD odds ratios (ORs) and 95% confidence intervals (CIs) through two hierarchical models: Model 1 (adjusted for age, gender, income) and Model 2 (Model 1 + BMI). Statistical significance was set at p < 0.05, with analyses performed in SPSS version 21. Overall, 200 ADHD and 300 healthy children participated in this study. Energy-adjusted dietary inflammatory index (E-DII) was directly associated with ADHD risk in the crude model (OR = 1.104; 95% CI: 1.009, 1.208; p = 0.031). This result also remained significant in Model 1 (OR = 1.162; 95% CI: 1.050, 1.285; p = 0.004) and Model 2 (OR = 1.133; 95% CI: 1.021, 1.258; p = 0.019). We found that E-DII had a significant association with the risk of ADHD in Iranian children. Limitations include the case-control design, which precludes causal inference, and potential residual confounding from unmeasured factors. It will be necessary to conduct further studies to confirm these findings.